Basic Thermochemistry in Materials Processing - Plascencia, Gabriel; Jaramillo, David (Springer International Publishing : Imprint: Springer, 2017)
This book provides the reader with some thermochemistry notes. The intention is to provide a simple, easy to understand text which serves as a complimentary material to more complex books. It also provide students and those beginning in the field with several application examples used in different areas of materials processing. The book presents fully solved problems, some quite often found in major metallurgical operations.
Keywords: Materials science.; Physical chemistry.; Thermodynamics.; Heat engineering.; Heat transfer.; Mass transfer.; Engineering -- Materials.; Metals.; elektronické knihy; electronic books